Structural and copy number chromosome abnormalities in canine cutaneous mast cell tumours - Vozdova, Miluse; Kubickova, Svatava; Cernohorska, Halina; Fröhlich, Jan; Fictum, Petr; Rubes, Jiri (Journal of applied genetics, 2019)
Mast cell tumours (MCTs) are the most common skin tumours in dogs. Their clinical behaviour is variable and their aetiology remains largely unknown. We performed a metaphase fluorescence in situ hybridisation (FISH) with whole chromosome painting probes, and interphase FISH with BAC probes for 14 cancer-related genes to reveal clonal structural chromosome rearrangements and copy number variants (CNVs) in canine cutaneous MCTs. The metaphase FISH performed in three MCTs revealed several clonal monosomies and trisomies and two different chromosome rearrangements. No centric fusions were detected. The interphase FISH showed a variety of low frequency CNVs for the individual cancer-related genes. The heterogeneous character of the detected abnormalities indicates increased chromosome instability in canine MCTs. The clonal gain of chromosome 11 was detected in 81% (13/16) of the MCTs. Further research is needed to evaluate the significance of this abnormality as prognostic factor for the survival time or recurrence risk assessments in canine cutaneous MCTs.
Keywords: Chromosome rearrangement; Male; Dogs; Mast Cells; hybridizace in situ fluorescenční; Chromosome Painting; Skin Neoplasms; chromozomální aberace; Cancer; Trisomy; mužské pohlaví; Copy number variant; Monosomy; Mast cell tumour; Chromosome Aberrations; Animals; ženské pohlaví; zvířata; mastocyty; Dog Diseases; Dog; nemoci psů; In Situ Hybridization, Fluorescence; psi; nádory kůže; Female; Chromosome; malování chromozomů